Elevated end‐diastolic wall stress after acute myocardial infarction predicts adverse cardiovascular outcomes and longer hospital length of stay. Issue 11 (16th September 2018) - Mosleh, Wassim; Elango, Kalaimani; Shah, Tanvi; Chaudhari, Milind; Gandhi, Sumeet; Kattel, Sharma; Karki, Roshan; Khalil, Charl; Frodey, Kevin; Dahal, Suraj; Okeeffe, Cale; Aljebaje, Zaid; et al.
Abstract : Background: Acute myocardial infarction (MI) leads to ventricular remodeling in response to oxygen demand. Such changes include left ventricular (LV) dilatation and increased myocardial wall stress. Prior studies showed that wall stress is a vital parameter of cardiac remodeling. However, outcome data are lacking. We aim to investigate wall stress post‐MI in relation to biomarkers of cardiac remodeling and cardiovascular outcomes. Methods: Patients presenting with ST‐elevation MI (STEMI) requiring primary percutaneous intervention (PCI) were enrolled prospectively. LVEF and volume‐based end‐diastolic (EDWS) and end‐systolic (ESWS) wall stress were measured from predischarge echocardiograms. Serum samples were collected for measurement of serum biomarkers. We identified 81 patients meeting inclusion criteria (64% men, 36% women) with a mean age of 61. The primary outcome was major adverse cardiovascular events (MACE) defined as 1‐year composite endpoint of cardiac mortality, recurrent MI, revascularization, or stroke. Length of hospitalization (LOH) was recorded. Results: Major adverse cardiovascular events‐positive patients (n = 12) had significantly higher EDWS levels (15.87 vs 12.33, P  = 0.045), and galectin‐3 levels (19.07 vs 11.75, P  = 0.015), and lower LVEF (40.0% vs 48.4%, P  = 0.023) compared to MACE‐negative patients. Patients with LOH > 72 hours (n = 33) had significantly higher EDWS, galectin‐3, and peak troponin, and lower LVEF compared to patients with LOH < 72 hours. EDWS positively correlated with LOH and galectin‐3. EDWS was an independent predictor of MACE by binomial regression analysis. Conclusion: End‐diastolic walls tress is a potential prognostic tool for risk stratifying STEMI patients, providing an assessment of the functional consequences of myocardial remodeling. It is predictive of MACE independent of LVEF, associated with longer hospitalizations, and correlates with galectin‐3, a biomarker of cardiac remodeling.